Ambulatory sagittal split ramus osteotomy: strategy for enhanced recovery after surgery. Issue 4 (April 2023) - Hattori, Y.; Uda, H.; Niu, A.; Yoshimura, K.; Sugawara, Y.
Abstract: The sagittal split ramus osteotomy (SSRO) has been performed mainly on an inpatient basis because of the duration of anaesthesia and the potential risk of postoperative complications, such as bleeding, pain, nausea, and vomiting. However, advances in both surgical and anaesthetic management have enabled the reduction of these risks and shortened the length of hospital stay. Thus, the SSRO may be feasible even in the ambulatory setting in elective cases. The clinical records of all patients who underwent an outpatient SSRO between August 2011 and September 2020 at Lilla Craniofacial Clinic were reviewed retrospectively. Data on age, sex, duration of surgery, operative procedures, intraoperative bleeding, and admission status were investigated. In total, 143 patients underwent a bilateral SSRO. The SSRO was performed as an isolated procedure in 73 patients and concomitantly with other surgical procedures in the remaining 70 patients. Overall, 142 of the 143 patients were discharged on the day of surgery (99.3%); only one (0.7%) required an overnight stay because of a submental haemorrhage after genioplasty. No emergency hospitalizations or readmissions occurred after discharge. Multimodal perioperative management, both surgical and anaesthetic, facilitated enhanced patient recovery after surgery, and SSRO was performed successfully and safely as an ambulatory procedure.